2011
DOI: 10.1002/nau.21154
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for autonomic nervous system dysfunction in females with idiopathic overactive bladder syndrome

Abstract: These results suggest ANS dysfunction, predominantly a sympathetic ANS dysfunction, is associated with iOAB, specifically in patients with iOAB without DO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
0
37
2
Order By: Relevance
“…For instance, insulin resistance, the underlying mechanism of metabolic syndrome, and nicotine abuse may contribute to LUTS by sympathetic overactivity. Sympathetic overactivity is the main neuropathological finding in females with idiopathic OAB [25] and increased sympathetic activity of the bladder neck and prostate is also an independent aetiological factor for the development of LUTS in men [26].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, insulin resistance, the underlying mechanism of metabolic syndrome, and nicotine abuse may contribute to LUTS by sympathetic overactivity. Sympathetic overactivity is the main neuropathological finding in females with idiopathic OAB [25] and increased sympathetic activity of the bladder neck and prostate is also an independent aetiological factor for the development of LUTS in men [26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hubeaux et al [12] reported that sympathetic overactivity is the main neuropathologic finding in patients with idiopathic OAB. Increased sympathetic activity of the bladder neck and prostate is also an independent etiologic factor for the development of LUTS in men [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some components of LUTS have been linked to metabolic syndrome [5], and thus carry common risk factors for cardiovascular disease. LUTS might precipitate the development of cardiovascular events through multifactorial interlacing processes such as autonomic nervous dysfunction [6], [7], affective disorders [8], or adverse effects of medications for treating LUTS [9], [10]. However, the magnitude of the LUTS burden on the medical care for cardiovascular disease in a population scale remains unclear.…”
Section: Introductionmentioning
confidence: 99%